Volatile constituents of the leaves of Siparuna thecaphora (Siparunaceae) from Turrialba, Costa Rica - Cicció, José F (2002)
The composition of the essential oil from leaves of Siparuna thecaphora (Poepp. et Endl.) A. DC. collected in Turrialba, Costa Rica, was determined by capillary GC/MS. Seventy-six compounds were identified corresponding to ca. 95% of the oil. The major components were germacrene D (32.7%), a-pinene (16.3%), b- pinene (13.8%) and b-caryophyllene (4.1%). Thirty-one minor compounds were identified for the first time in this genus of plants.